Shift in Sabella spallanzanii (Polychaeta, Sabellidae) spawning period in the Central Mediterranean Sea: a consequence of climate change? - GIANGRANDE, A.; LICCIANO, M.; MUSCO, L.; STABILI, L. (Mediterranean Marine Science, 2010)
Sabella spallanzanii is a large tubicolous filter feeder polychaete common in the Mediterranean fouling assemblages where it plays an important role in structuring the community. Its reproductive biology is well known and had been investigated since 1993. During the past few years a shift in its reproductive period has been observed. In 2008 the presence of ripe eggs in the females was observed at least two months in advance compared to the past. This was confirmed during the 2009 when spawning and fertilization were observed three months in advance compared to the past. Possible causes of this shift may be related to the increasing surface temperature in the Central Mediterranean Sea.